Somatic symptom disorder was common in children and adolescents attending an emergency department complaining of pain. - Cozzi, Giorgio; Minute, Marta; Skabar, Aldo; Pirrone, Angela; Jaber, Mohamad; Neri, Elena; Montico, Marcella; Ventura, Alessandro; Barbi, Egidio (Acta Paediatr, 2017)
AIM: The aim of this study was to quantify the prevalence of somatic pain in a paediatric emergency department (ED). METHODS: We conducted a prospective observational study using patients admitted to the ED of an Italian children's hospital between December 2014 and February 2015. We enrolled children aged 7-17 who turned up at the ED complaining of pain. Patients and parents were asked to fill in a questionnaire to allow the analysis of the patients' medical history and provide contact details for follow-up. We divided the enrolled patients into four groups: post-traumatic pain, organic pain, functional pain and somatic pain. The questionnaire was used to define pain characteristics and to generate an impairment score. RESULTS: Of the 713 patients who met inclusion criteria, 306 (42.9%) were enrolled in the study. Of these, 135 (44.0%) suffered from post-traumatic pain, 104 (34.0%) from organic pain, 41 (13.4%) from functional pain and 26 (8.6%) from somatic pain. Somatic pain patients had endured pain longer, had missed more school days and had suffered severe functional impairment. CONCLUSION: This study highlighted that somatic pain was a significant contributor to paediatric emergency room visits and should be suspected and diagnosed in children reporting pain.
Keywords: Adolescent; Child; Emergency Service, Hospital; Female; Humans; Italy; Male; Medically Unexplained Symptoms; Pain; Prospective Studies